ANALISIS KEMANDIRIAN SISWA DI ERA NEW NORMAL (Universitas PGRI Sumatera Barat, 2022)
Abstract The independence of students in the new normal era is needed to be able to understand the subject matter in order to achieve the desired learning goals. This research is motivated by the low learning independence of students when studying online. The purpose of this study was to determine the description of student learning independence in the new normal era of class X science at Madrasah Aliyah Swasta (MAS) Lubuk Malako, South Solok Regency. The research method used is descriptive method using a qualitative approach. The sampling technique used is purposive sampling. The instruments used to collect data are in the form of student learning independence questionnaires and interviews. The test results were analyzed based on the assessment criteria, namely high, medium, low, and very low. The results showed that students' learning independence in the new normal era of class X IPA was moderate because of the 8 indicators of student learning independence, there were 3 indicators of students who answered incompletely, namely indicators of learning initiative, difficulty seeing. as a challenge, and utilize and seek relevant sources.